Is Anteromedial Drilling Safe in Transphyseal Anterior Cruciate Ligament Reconstruction in Adolescents with Growth Remaining?. Issue 4 (April 2019) - Mathew, Stephen; Ellis, Henry B.; Wyatt, Charles W.; Sabatino, Meagan J.; Zynda, Aaron J.; Dennis, Garrett; Wilson, Philip L.
Abstract : Background: Previous reports of transphyseal drilling in anterior cruciate ligament (ACL) reconstruction have demonstrated good clinical outcomes without subjective changes in further skeletal development. The purpose of this study is to evaluate radiographic changes during continued growth following a transphyseal ACL reconstruction using an anteromedial femoral (AM) drilling technique in patients with >18 months of growth remaining. Methods: A review of consecutive adolescents who underwent a soft tissue transphyseal ACL reconstruction using an AM drilling technique was performed. Inclusion criteria was 18 months of growth remaining based on radiographic bone age and standing radiographs at least one year from the index procedure. Demographic, preoperative, and postoperative data, and follow-up three-foot standing lower extremity radiographs were reviewed. Radiographic data included femoral length, tibial length, total lower extremity length, mechanical axis deviation (MAD), lateral distal femoral angle (LDFA), and medial proximal tibial angle (MPTA). Results: In total 12 adolescent patients with a mean age of 13.4 years (range, 12.3 to 14.4) and bone age of 13.4 years (11.5 to 14) at the time of surgery were included. At an average of 2.27-year follow-up (412 to 1058 d), there was no difference in the total growth of the operative and nonoperative limb (48.5 mm vs. 47 mm; P =0.36). In addition, the average increases in femoral length (23.4 mm) and tibial length (25.8 mm) were not statistically different between the operative and the nonoperative limb ( P =0.12; P =0.75). There was no statistical difference in mechanical axis deviation, LDFA, or MPTA between preoperative and postoperative radiographs. Mean differences in operative and nonoperative coronal angular changes were all <1.5 degrees. Conclusions: With at least 2 years of growth remaining, transphyseal ACL reconstruction with anteromedial drilling did not significantly affect the physis or residual growth compared with the contralateral extremity. Although this technique may create a larger defect in the physis, standing radiographs demonstrate there is no change in limb length or angulation in growing adolescents approximately 2 years after surgery. Level of Evidence: This is a case series; Level IV evidence.